ANALISIS PENENTUAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN METODE FULL COSTING DAN VARIABLE COSTING PADA PEMBUATAN ABON IKAN - Nurlaila Hasmi (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to determine the suitability of the method of determining the cost of production at PT. Prima Istiqamah Sejahtera uses the full costing method with variable costing. This type of research is qualitative research with a comparative descriptive approach. Sources of data used in this study are primary data and secondary data. Primary data collection is done by direct survey method at the research location using observation, interview, and documentation techniques. While secondary data collection is done by collecting and understanding literature that is relevant to the problem being studied to get an explanation of the research problem. Data were analyzed using a comparative descriptive approach regression that is by explaining and comparing between the methods of determining the cost of production at PT. Prima Istiqamah Sejahtera uses the full cosing method with variable costing. The results showed that the results of the calculation of the cost of production carried out by PT. Prima Istiqamah Sejahtera is relatively low compared to the full costing method and variable costing. In addition, there are differences in the calculation of the cost of production of shredded fish according to PT. Prima Istiqamah Sejahtera with the full costing method and variable costing, this happens because of differences in the cost incurred.